ANALISIS STRUKTURALISME DAN NILAI SOSIAL DALAM NOVEL SERENDIPITY KARYA ERISCA FEBRIANI SEBAGAI BAHAN AJAR SASTRA DI SMA - Tiranita, Ghadis; Saddhono, Kundharu (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This study aims to analyze the novel "Serendipity" by Erisca Febriani using qualitative research methods. The novel will be examined from a structuralism perspective and identify the social values contained within it, as well as explore its potential as a literature teaching material at the high school level. The structuralism approach is used to dissect the intrinsic elements of the novel. Furthermore, the analysis of social values focuses on the moral, ethical, and social messages represented through the behavior and interactions of the characters. The results of the study show that "Serendipity" has a strong narrative structure and is rich in social values such as friendship, love, struggle, and sacrifice. These values are relevant to the lives of teenagers and are highly beneficial if integrated into literature education in high schools. Using this novel as teaching material can enhance students' appreciation of Indonesian literary works and instill positive values in their daily lives. Thus, this study recommends the use of "Serendipity" as an effective and inspiring alternative teaching material in the high school literature curriculum. Keywords: Structuralism, social values, novel, teaching material, high school